GENDER AND PARTICIPATORY DEMOCRACY IN NIGERIAN FOURTH REPUBLIC: THE LOCAL GOVERNMENT SYSTEM IN PERSPECTIVE - Ihemadu, Michael Chinazam; Njoku, Benedict Nnamdi (African Journal of Social and Behavioural Sciences, 2023)
The study examines the impact of gender discrimination on participatory democracy in the local government system in Nigeria’s Fourth Republic. This phenomenon no doubt, has continued to create intense academic discourse. The situation at the local government level is rather worrisome. The gap between male and females in both political participation and representation at the local level across the country is unimaginably high, notwithstanding the present democratic dispensation that came on board in 1999. Measures put in place to check-mate this abnormality are yet to yield the much-desired positive results. The study adopted a qualitative approach with data collected from secondary sources only. The specific objectives of the study are to determine the impact of gender discrimination on participatory democracy at the local government level in Nigeria; examine the factors that encourage gender inequality in participatory democracy at the local government level and determine why the measures put in place as panacea to the problem have failed. The glass ceiling theory was used to describe the phenomenon under investigation. The findings amongst others show that political participation at the local government system in Nigeria is lopsided in favour of the male gender to the detriment of the female folk whose interest in participating actively in grassroots politics by vying for elective positions has been greatly eroded. It was recommended amongst others that such negative tendencies like continuous intimidation, harassment, violence, threats, and money politics that have characterized the participatory democracy at the local level in the country should be stopped forthwith through improvement in our electoral laws and processes.